갑상샘 세침흡인 세포검사와 조직검사의 진단 일치율 및 정확도 분석 -조직학적으로 확진된 322 예에 대한 분석 - 구자승; 정우희; 양석우; 홍순원; Koo, Ja-Seung; Jung, Woo-Hee; Yang, Seok-Woo; Hong, Soon-Won (Taehan Sepo Pyŏngri Hakhoe chi, 2008)
Fine needle aspiration (FNA) cytology is the decisive test in the pre-operative diagnostics of thyroid nodules. Here we share our institutional experience about thyroid aspiration and give suggestions for suspicious cytology results. Three hundred twenty-two cases in 270 patients (mean age 47.4 years, 243 women and 27 men) who underwent thyroidectomy were reviewed. Among the 322 cases, the FNA diagnosis of "positive for malignancy" was 87 cases (27.0%), "suggestive of malignancy" 30 cases (9.3%), "suspicious for malignancy" 61 cases (18.9%), "negative for malignancy" 102 cases (31.7%), and "unsatisfactory smear" 42 cases (13.0%). Eighty seven cases (100%) out of "positive for malignancy", 29 cases (96.7%) out of "suggestive of malignancy", and 39 cases (64.0%) out of "suspicious for malignancy" were papillary carcinoma (148 cases, 95.5%), or follicular carcinoma (2 cases, 1.3%), or metastatic carcinoma (1 case, 0.6%). Seventeen patients who had only negative or unsatisfactory cytology underwent thyroidectomy and nine cases (52.9%) were papillary carcinoma. We suggest that: the cytology diagnosis of "suggestive of malignancy" could be regarded as "positive for malignancy", the cytology diagnosis of "suspicious of malignancy" should be carefully correlated with clinico-radiologic manifestation, and even a negative or unsatisfactory smear should be carefully followed up.